Answer :



Equating both equations


6u – 2v = 2u + 6v


u = 2v


Substituting value of u


2(6v – v) = 5 × 2v × v


v = 1


Thus, 2(3u – 1) = 5u


6u – 2 = 5u


u = 2


Rate this question :

How useful is this solution?
We strive to provide quality solutions. Please rate us to serve you better.
Related Videos
Merchant of Venice (Summary and Important Questions)Merchant of Venice (Summary and Important Questions)Merchant of Venice (Summary and Important Questions)30 mins
Try our Mini CourseMaster Important Topics in 7 DaysLearn from IITians, NITians, Doctors & Academic Experts
Dedicated counsellor for each student
24X7 Doubt Resolution
Daily Report Card
Detailed Performance Evaluation
caricature
view all courses
RELATED QUESTIONS :

Solve each of theRS Aggarwal - Mathematics

If 2x – 3y = 7 anRD Sharma - Mathematics

Solve the followiRD Sharma - Mathematics

Solve each of theRD Sharma - Mathematics